2010
DOI: 10.1016/j.gca.2010.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for equilibrium iron isotope fractionation by nitrate-reducing iron(II)-oxidizing bacteria

Abstract: Iron isotope fractionations produced during chemical and biological Fe(II) oxidation are sensitive to the proportions and nature of dissolved and solid-phase Fe species present, as well as the extent of isotopic exchange between precipitates and aqueous Fe. Iron isotopes therefore potentially constrain the mechanisms and pathways of Fe redox transformations in modern and ancient environments. In the present study, we followed in batch experiments Fe isotope fractionations between Fe(II) aq and Fe(III) oxide/hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 53 publications
(116 reference statements)
4
43
2
1
Order By: Relevance
“…In a series of publications (21,22,32,38), Kappler and coworkers have also described formation of Fe(III) oxyhydroxides precipitates both externally and in the periplasm of Acidovorax strain BoFeN1 and have suggested Fe(II) oxidation occurs periplasmically. We believe that the encrustations formed with Fe 2ϩ in batch reactors are artifacts of the millimolar-level Fe 2ϩ and NO 3 Ϫ concentrations typically used in Ϫ and Fe 2ϩ sorbed onto cell surfaces (7,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of publications (21,22,32,38), Kappler and coworkers have also described formation of Fe(III) oxyhydroxides precipitates both externally and in the periplasm of Acidovorax strain BoFeN1 and have suggested Fe(II) oxidation occurs periplasmically. We believe that the encrustations formed with Fe 2ϩ in batch reactors are artifacts of the millimolar-level Fe 2ϩ and NO 3 Ϫ concentrations typically used in Ϫ and Fe 2ϩ sorbed onto cell surfaces (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…Microbially driven, Fe(III)/Fe(II) redox transitions in the environment have a dramatic impact on iron's solubility, mineralogy, sorption characteristics, and overall geochemical properties (21,29,45). Microbially mediated redox transformations of Fe can also affect the biogeochemical cycling of other key nutrients (e.g., C, S, P, and N) (15,29), trace metals (9,49), metalloids (12), and the fate of organic pollutants (25) and contaminant metals (8), including those released from industrial and mining areas (30).…”
mentioning
confidence: 99%
“…2 Because biological enzymes are known to prefer lighter isotopes as substrates, it was initially anticipated that direct, biologically-catalyzed Fe-redox reactions may impart a fractionation between the substrate and product (Beard et al, 1999). In experiments and natural samples of abiotic and biological Fe(II) oxidation at neutral pH, Fe(III) ppt , i.e., the product of Fe(II) oxidation, is actually isotopically heavier than Fe(II) aq by about 1-3& Balci et al, 2006;Croal et al, 2009;Kappler et al, 2010), due to kinetic effects during rapid precipitation and the formation of stronger bonds in precipitates relative to aqueous phases. If precipitation is slow, equilibrium isotope exchange between Fe(II) aq and Fe(III) aq may be attained, increasing the magnitude of fractionations between Fe(II) aq and Fe(III) ppt (Johnson et al, 2002;Anbar et al, 2005;Balci et al, 2006), but this is not likely significant during rapid precipitation at circumneutral pH.…”
Section: Introductionmentioning
confidence: 99%
“…Other important processes of Fe isotope fractionation are the adsorption of heavy Fe isotopes onto the surfaces of Fe oxides like goethite (e.g., Beard et al 2010;Icopini et al 2004;Jang et al 2008;Mikutta et al 2009) and slow mineral transformations, e.g., of ferrrihydrite to goethite or siderite to goethite (Clayton et al 2005;Wiesli et al 2004). Moreover, bacteria that reduce Fe III to gain energy (e.g., Beard et al 1999Beard et al , 2003Brantley et al 2001Brantley et al , 2004Crosby et al 2005;Icopini et al 2004) or oxidize Fe II (e.g., Croal et al 2004;Kappler et al 2010) have been shown to fractionate Fe isotopes during the process of reduction and oxidation, respectively. Here, the heavy Fe isotopes are being incorporated preferentially by the bacteria, leaving an isotopically light aqueous solution and a comparatively heavy soil horizon behind (e.g., Wiederhold et al 2007b).…”
Section: Introductionmentioning
confidence: 99%